Associations of parental disability with child educational attainment - Zeng, Lijie; Wertz, Jasmin; Auyeung, Bonnie; Marryat, Louise (International Journal of Population Data Science, 2025)
Objectives Little is known about how disability of one generation might affect the educational outcomes of the next generation. This research aims to examine the epidemiology of disability among parents and the associations of parental disability with children’s educational attainment in England between 2001 and 2018, using linked survey-administrative data. Method We used data from the National Pupil Database (NPD) linked to the UK Millennium Cohort Study (MCS). This research included MCS families with singleton children born in 2000/01 followed up to age 17 years in England. Disability was measured by parental self-report of limiting longstanding illness in 2001, 2006, 2008, 2012 and 2015. Attainment was assessed based on test scores and national threshold levels in the Reception year, Key Stages 1, 2 and 4. We examined the associations of parental disability with child attainment over time using descriptive statistics and regression models, adjusting for individual, familial, socioeconomic and geographical confounders. Results The prevalence of disability among parents increased between 2001 and 2015, and disabled parents were at greater risk of health, socioeconomic and geographical disparities. For both sexes combined, musculoskeletal and respiratory disorders were the leading causes of parental disability counts in 2001, while mobility and mental health conditions were the leading causes in 2015. We also observed dynamic changes in the status of parental disability. Children exposed to parental disability were more likely to experience worse attainment outcomes, compared with those without having a disabled parent. The negative associations between parental disability and child attainment varied by sex. Analyses are ongoing and results will be finalised by the conference date. Conclusion Our findings showed an increasing rate of parents with disabilities between 2001 and 2015. Parental disability was negatively associated with children’s educational attainment over time. Policies and services should be tailored to effectively support this population in need.